Analisis Tingkat Kesiapsiagaan Siswa Dalam Menghadapi Bencana Kebakaran di SMAN 50 Jakarta - Arizqeine Pawiranata; Cahyadi Setiawan (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2023)
SMAN 50 Jakarta is one of the schools located in a fire-prone area, this is due to the location of the school which is in an area with a high frequency of fires, which is in Cipinang Muara Village, Jatinegara District, East Jakarta. This research aims to determine the level of preparedness of class XI students at SMAN 50 Jakarta in dealing with fire disasters. This study uses a quantitative method with a scoring analysis technique based on Lipi/Unesco and the National Disaster Management Agency using five disaster preparedness parameters, namely knowledge and attitudes, policies, emergency response plans, early warning systems, and resource mobilization. This research is a population research with a total of 198 students. This research was conducted in January - March 2023. The results of the research showed that class XI students at SMAN 50 Jakarta had a preparedness index score of 73.75, which means students have a moderate level of preparedness. With a score for each parameter, namely, knowledge and attitudes get a score of 70, policy with a score of 98, emergency response plan with a score of 84, disaster warning system with a score of 86, and resource mobilization with a score of 87. From the results of the research that has been done, it can be concluded that students class XI at SMAN 50 Jakarta needs to improve fire disaster preparedness, especially on the parameters of knowledge and attitudes